David N. Weil. Economic Growth. (Second Edition). New York: Addison Wesley Press, 2009. 565 pages. Paperback. Price not given. (The Pakistan Development Review, 2008)
Despite the great concern towards the issue of the convergence of economies, the world is still witnessing the gap between rich and poor being widened progressively. The book examines the interesting question of why some countries are rich and some are poor-why they differ in their levels of income and their rates of economic growth. Featuring the latest data, new case studies, and a number of significant additions in the content, the new Second Edition takes the Weil legacy further. The text develops a very balanced relevance of both macroeconomics’ classical roots and its current practice in the field of growth. Engagingly written, it brings into use simple models, close to reality examples, and instructive tables and figures to address the key issues. Chapter summaries, list of key concepts at the beginning of each chapter, questions for review, as well as problems and applications to help the diligent reader master the material he provides. The clarity of the writing, the richness of the empirical and quantitative descriptions, and the best available evidence of some of the modern economies confronting growth issues, however, would further deepen his interest.